'Estimation of the moment redistribution and plastic hinge characteristics in two span beams cast with high-performance fiber reinforced Cementinious composite (HPFRCC). (January 2022) - Ehsani, Ramin; Sharbatdar, Mohammad Kazem; Kheyroddin, Ali
Abstract: In this article, the outcomes from an experiential program aimed at investigating the effect of high- performance fiber reinforced cementitious composite (HPFRCC) layers and stirrups distance on flexural performance, ductility, moment redistribution, and plastic hinge length of two-span continuous concrete beams. The unique characteristics of reinforced HPFRCC continuous beams. Under flexural loading, such as high resistance to splitting cracks, less rebar slippage, damage localization in a single or few flexural cracks, inelastic strain concentration within a small region of rebar, and failure by the fracture of tensile longitudinal reinforcement in the plastic hinge region motivated this research study. The specimens have rectangular cross section of 250 mm (height) × 200 mm (width) and are continuous over two spans of 1800 mm each and two concentrated equal statically monotonic loads are applied at the mid-span of each beam. Eight beams specimens divided into three groups A, B and C were designed and cast due to the type of concrete and the stirrup spacing. Group A, consisted of two normal concrete beams with conventional stirrup spacing (d/2) (reference specimen) and compact stirrup spacing (d/4), and Group B consisted of four continuous beams made of high- performance fiber reinforced cementitious composite (HPFRCC) were layered with conventional stirrup spacing stirrups (d/2), and Group C, consisted of two continuous beams made of completely high- performance fiber reinforced cementitious composite(HPFRCC) with conventional (d/2) and compact stirrups spacing (d/4). The test results indicated that application of HPFRCC instead of conventional concrete in different section of beams with compact stirrups in critical length induced to increasing the ductility of Continuous beams. It can also be seen that increasing the transverse reinforcement, had a positive effect on the achieved moment redistribution compared with the reference beam with conventional spacing transverse reinforcement. In flexure, a highly nonlinear plastic strain distribution of the primary tensile reinforcement is observed at dominant crack locations, leading to significant differences in plastic hinge length and behavior as compared to ordinary reinforced concrete flexural members.